Performance of a subject composition in engineering of oil painting. Stages of work above the diploma - O.S. Yurchenko (Academy of Cognitive and Natural Sciences, 2009)
in clause the problem of creation of conditions of the system approach is considered at creation of a subject composition and development of creative abilities of the students in a context of work above the degree task.